Social identity, core self-evaluation, school adaptation, and mental health problems in migrant children in China: a chain mediation model - Chen, Ye; Yu, Xinxin; Ma’rof, Aini Azeqa; Zaremohzzabieh, Zeinab; Abdullah, Haslinda; Halimatusaadiah Hamsan, Hanina; Zhang, Lyuci (MDPI, 2022)
(1) Background: The present study investigated the relationships between social identity, core self-evaluation, school adaptation, and mental health problems in migrant children, and the mechanism underlying these relationships; (2) Methods: The participants were migrant middle school students in China. Data analysis was conducted using SPSS version 26. A survey comprising the social identity scale, core self-evaluation scale, school adaptation scale, and mental health scale MMHI-60 was deployed; (3) Results: Findings indicated a significant and negative association between social identity and mental health problems, and such an association was sequentially mediated by core self-evaluation and school adaptation. Furthermore, core self-evaluation and school adaptation played a chain mediation role between social identity and migrant children’s mental health problems; (4) Conclusions: It is crucial to improve social identity, core self-evaluation, and school adaptation to reduce mental health problems among this population. Therefore, the research results provide a new direction for promoting the development of mental health education for migrant workers and their children in China.